2012
DOI: 10.1101/lm.023523.111
|View full text |Cite
|
Sign up to set email alerts
|

Visual landmarks facilitate rodent spatial navigation in virtual reality environments

Abstract: Because many different sensory modalities contribute to spatial learning in rodents, it has been difficult to determine whether spatial navigation can be guided solely by visual cues. Rodents moving within physical environments with visual cues engage a variety of nonvisual sensory systems that cannot be easily inhibited without lesioning brain areas. Virtual reality offers a unique approach to ask whether visual landmark cues alone are sufficient to improve performance in a spatial task. We found that mice co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 40 publications
0
61
0
Order By: Relevance
“…However, there is no agreement on which is more important and how these signals combine to generate spatially localized place cell firing and its temporal organization with respect to the theta rhythm (24). Recent studies showed that mice could navigate in a virtual environment (VE) and a small sample of place cells has been recorded in mice running on a virtual linear track (25)(26)(27). VE affords the opportunity to isolate the visual environment and internal movement-related information from other sensory information, and to study their contributions to place cell firing.…”
mentioning
confidence: 99%
“…However, there is no agreement on which is more important and how these signals combine to generate spatially localized place cell firing and its temporal organization with respect to the theta rhythm (24). Recent studies showed that mice could navigate in a virtual environment (VE) and a small sample of place cells has been recorded in mice running on a virtual linear track (25)(26)(27). VE affords the opportunity to isolate the visual environment and internal movement-related information from other sensory information, and to study their contributions to place cell firing.…”
mentioning
confidence: 99%
“…On the other hands, some basic biological, pharmacological and toxicological information changes after antidepressant treatments, such as optogenetic studies [25,26] or genetic engineering mice (GEM) [27] and other new technologies and patents must also be used to assess many opening hypotheses and systematic scientific studies, including this one and finally update antidepressant therapy PG and other clinical diagnostic and therapeutic systems. The techniques of optogenetic and genetic engineering mice (GEM) are new endeavors that can be used to study the functions and dysfunctions of specific genes in living bodies.…”
Section: Other Technologymentioning
confidence: 99%
“…In spite of the great success of these VR setups, there were only few attempts to train animals to carry out more complex navigational tasks in virtual environments [23,24]. Behavioral paradigms in virtual realities for rodents mostly made use of open fields [13], linear tracks [14,15,17,25] or were limited to providing optical flow [16,22] and spatially unrelated visual stimuli [26]. Moreover, subtle differences in the neuronal space codes have been reported between running in real worlds http://dx.doi.org/10.1016/j.bbr.2014.03.007 0166-4328/© 2014 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%